Richard Seaford. Reciprocity and Ritual. Homer and Tragedy in the Developing City-State, Oxford, Clarendon Press, 1995, 455 pp. - Chazarreta, Daniela Evangelina (1997)
Fil: Chazarreta, Daniela Evangelina. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.